BMP6-induced modulation of the tumor micro-milieu - Stieglitz, David; Lamm, Susanne; Braig, Simone; Feuerer, Lena; Kuphal, Silke; Dietrich, Peter; Arndt, Stephanie; Echtenacher, Bernd; Hellerbrand, Claus; Karrer, Sigrid; Boßerhoff, Anja Katrin (Oncogene, 2019)
Melanoma is the deadliest form of skin cancer with rising incidence, creating a significant health problem. We discovered increased expression of bone morphogenetic protein 6 (BMP6) in melanoma cells and tissues, and observed that BMP6 deficiency caused significantly delayed tumor onset and decelerated tumor progression in a melanoma mouse model. Moreover, we determined that BMP6 inhibits dermal mast cell recruitment and found that mast cell-derived mediators significantly reduced melanoma growth in vitro. In line with this, mast cell deficiency accelerated tumor onset and progression in a melanoma mouse model. Analysis of human melanoma tissues revealed a strong negative correlation between melanoma proliferation and mast cell infiltration. This study elucidates a novel role of BMP6-induced modulation of the tumor microenvironment.
EVALuna2:106826

Role of melanoma inhibitory activity in melanocyte senescence - Feuerer, Lena; Lamm, Susanne; Henz, Ingmar; Kappelmann-Fenzl, Melanie; Haferkamp, Sebastian; Meierjohann, Svenja; Hellerbrand, Claus; Kuphal, Silke; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2019)
The protein melanoma inhibitory activity (MIA) is known to be expressed in melanoma and to support melanoma progression. Interestingly, previous studies also observed the expression of MIA in nevi. Concentrating on these findings, we revealed that MIA expression is correlated with a senescent state in melanocytes. Induction of replicative or oncogene-induced senescence resulted in increased MIA expression in vitro. Notably, MIA knockdown in senescent melanocytes reduced the percentage of senescence-associated beta-Gal-positive cells and enhanced proliferation. Using the melanoma mouse model Tg(Grm1), MIA-deficient mice supported the impact of MIA on senescence by showing a significantly earlier tumor onset compared to controls. In melanocytes, MIA knockdown led to a downregulation of the cell cycle inhibitor p21 in vitro and in vivo. In contrast, after induction of hTERT in human melanoma cells, p21 regulation by MIA was lost. In summary, our data show for the first time that MIA is a regulator of cellular senescence in human and murine melanocytes.
CRIS-Team Scopus Importer:2019-07-02
Keywords: melanocyte; melanoma inhibitory activity; oncogene-induced senescence; p21; senescence; telomerase